2020
DOI: 10.31557/apjcc.2020.5.3.125-131
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Patients’ Perspectives on Integrating Cancer Care in Primary Care Settings: A Qualitative Inquiry

Abstract: Introduction: Research has demonstrated the importance of general practitioners in providing care for cancer patients within the concept of ‘care closer to home’. This study reports cancer patients’ views and expectations on integrated cancer care in primary care settings in Brunei. Methods: A qualitative approach using semi-structured in-depth interviews with cancer patients were conducted. The interviews were recorded, transcribed, and analysed using thematic analysis. Results: 13 cancer patients participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Due to many challenges, PC is not integrated into the health system of Iran, and scattered activities are carried out in this direction (Eshaghian-dorcheh et al, 2019;Rassouli et al, 2019a). In fact, integrating cancer care into the health system can save up about 70% of health system costs (Idris et al, 2020). Studies have shown that early integration of PC for cancer patients will lead to increased survival (Thakur and Ghoshal, 2019).…”
Section: Research Articlementioning
confidence: 99%
“…Due to many challenges, PC is not integrated into the health system of Iran, and scattered activities are carried out in this direction (Eshaghian-dorcheh et al, 2019;Rassouli et al, 2019a). In fact, integrating cancer care into the health system can save up about 70% of health system costs (Idris et al, 2020). Studies have shown that early integration of PC for cancer patients will lead to increased survival (Thakur and Ghoshal, 2019).…”
Section: Research Articlementioning
confidence: 99%
“…A delay in diagnosis is defined as a prolonged interval between the onset of the first symptom of cancer and the start of treatment while the case navigates the diagnostic pathway from patient to primary care and then secondary care (Andersen et al, 2009;Dobson et al, 2014). Although patients are generally accepting of the idea of primary care-based cancer care services due to added convenience and minimal waiting times, research shows that delays on the part of the patients themselves are often the main reasons for delays in cancer diagnoses (McLachlan et al, 2015;Idris et al, 2020). Most delays usually occur in the help-seeking interval between the appraisal of symptoms or bodily changes and consulting a doctor (McLachlan et al, 2015).…”
Section: Symptom Perceptions and Help-seeking Behaviours Of Omani Patmentioning
confidence: 99%
“…Palliative care (PC) is a vital care approach when it comes to life-threatening illnesses, the patients' lack of access to which is considered as a lack of human rights (Ansari et al, 2019). PC with the aim of improving the quality of life in patients and families has been emphasized by the World Health Organization (WHO) and the integration of these services into the health system is recommended to all countries (WHO, 2016;Idris et al, 2020). Palliative care should not be regarded as a luxury (Barasteh et al, 2020;Mishra et al, 2020).…”
Section: Introductionmentioning
confidence: 99%